Management of Chronic Hepatitis C: Consensus Guidelines - Morris Sherman; Stephen Shafran; Kelly Burak; Karen Doucette; Winnie Wong; Nigel Girgrah; Eric Yoshida; Eberhard Renner; Philip Wong; Marc Deschênes (Canadian Journal of Gastroenterology)
Since the last consensus conference on the management of chronic viral hepatitis, a number of studies looking at modifications of the standard course of treatment have been published. These changes have been sufficiently substantive to warrant review to determine whether any changes in the recommended treatment algorithms are needed. A consensus development conference was held in January 2007, and the present document highlights the results of the presentations and discussion about these issues. It reviews the epidemiology of hepatitis C in Canada, treatment of acute hepatitis C and new algorithms in chronic hepatitis C, including retreatment of previous treatment failures. In addition, sections on management of hepatitis C in special populations have been updated. There is also a section on the use of hematopoietic growth factors to help manage patients on therapy. The document should be read in conjunction with the previous document to identify changes. Some recommendations made in the previous document remain and are not discussed here.